North-south patterns within arboreal ant assemblages from rain forests in eastern Australia - Majer, Jonathan; Kitching, R.; Heterick, Brian E.; Hurley, K.; Brennan, K. (Wiley-Blackwell Publishing, Inc., 2001)
This paper describes the ant assemblages sampled from rain forest canopies ranging from southern Victoria through to Cape York Peninsula, Australia, and also in Brunei. Specifically, it examines the influence of decreasing latitude and variations in elevation on the character, richness, and abundance of the arboreal rain forest ant fauna, and also the relative contribution of ants to the total arthropod community. The sites that were examined included: cool temperate Nothofagus cunninghamii forest from a range of locations in Victoria; cool temperate N. moorei forest at both Werrikimbe and Styx River, New South Wales; notophyll vine forest in Lamington National Park, southeast Queensland; high elevation notophyll vine forest in Eungella National Park, central Queensland; complex notophyll vine forest at Robson Creek, Atherton Tablelands, north Queensland; complex mesophyll vine forest at Cape Tribulation, north Queensland; and mixed dipterocarp forest in Brunei. Although these sites represent a gradient increasingly tropical in character, botanically speaking, Eungella is less tropical than Lamington because of its high elevation. All samples were obtained by fogging the canopy with a rapid-knockdown pyrethrin pesticide. In all cases, circular funnels were suspended beneath the foliage of individual trees or small plots of mixed canopy. Arthropods were collected four hours after fogging.Following ordinal sorting, ants were identified and counted to morphospecies level. The resulting catch were then standardized across sites as numbers caught per 0.5 m2 sampling funnel. Generic and species richness were higher at the lowland tropical Cape Tribulation sites than at the sites to the south and was comparable with values in the Brunei site. Species richness was negatively correlated with latitude and elevation. Within the Australian rain forest, the lowland/highland break appears to be the strongest predictor of ant relative abundance, with a weaker latitudinal relationship superimposed.